20. \( x^{\frac{2}{3}}-5 x^{\frac{1}{3}}+6=0 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve the equation \( x^{\frac{2}{3}}-5 x^{\frac{1}{3}}+6=0 \), we can make a substitution. Let \( y = x^{\frac{1}{3}} \). The equation then becomes \( y^2 - 5y + 6 = 0 \). This is a quadratic equation, which can be factored as \( (y-2)(y-3)=0 \). Thus, the solutions for \( y \) are \( y=2 \) and \( y=3 \). Now substituting back for \( x \): 1. If \( y=2 \), then \( x^{\frac{1}{3}}=2 \) ⟹ \( x=2^3=8 \). 2. If \( y=3 \), then \( x^{\frac{1}{3}}=3 \) ⟹ \( x=3^3=27 \). Therefore, the solutions for \( x \) are \( x = 8 \) and \( x = 27 \).